Assessment of the performance of school-based multi-purpose teen centers in the first district of Iloilo Province. - Alba, Nina Charlyn B.; Anasario, JC Belle T.; Bautista, Aurora Fe C; Caliso, Femmy Rose E.; Catalan, Gabrielle A.; Espanol, Yzabel H.; Gonzaga, Royce Clea Maristel A.; Ilogon, Kent Paolo A.; Leoncio, Mabelle K.; Toledo, Mike T.; Vicencio, Geeza Gen S. (2017.)
Iloilo province is known to have high cases of teenage pregnancy in the Philippines, with the Municipality of Anilao topping since 2013. The STEP UP Project aims to lower the incidence of teenage pregnancy in Barangay Cag-an, Anilao, Iloilo through a positive developmental approach. It consists of a three-step intervention satisfying four component objectives during the six-week community immersion. Objective one is to organize a core group in both municipal and barangay level for the sustainability of the project which included the Local Government Unit of Anilao, barangay officials, and the teens and parents from the barangay. Objective two is to create a venue where teens can comfortably share their problems and sexuality wherein 13 teen facilitators were trained to aid in various activities planned for the project. Objective three is to increase knowledge, attitudes, and practices (KAP) on teenage pregnancy, adolescent health, and gender issues by 75% and with this, a pretest and posttest was administered to teens and parents to evaluate KAP. This resulted to a 6.97% (15.57-16.76) and 7.96% (17.51-18.91) increase in mean scores of teens and parents, respectively. The mean scores of both teens and parents were found to be statistically different at α 0.05 using paired T-test. Objective four is to help teens build confidence, improve their self-esteem, and persuade them to plan out for the future. Thus, a sport clinic was hosted and Buwas Damlag Fair was organized where different government agencies were invited to inspire the teens to pursue careers in the future. Overall, the project was a success since there is an increase of attendance by the parents and teens on activities and lectures, increase of mean scores in the pretest and posttest, and the objectives set were achieved. Implementation of this project to other barangays in Anilao is highly recommended.
Research Paper (Bachelor of Science in Public Health) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Adolescents -- Health -- Iloilo -- Research; Teen Center -- Iloilo -- Research